Analisis Perbandingan Kinerja Multiprotocol Label Switching dengan Mekanisme Label Distribution Protocol dan Traffic Engineering - Rahmat Yani; Primantara Hari Trisnawan; Mochammad Ali Fauzi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
MPLS is a forwarding method to forward a package together with the label attached to each package, this process is called label switching. Routing protocol mechanism to distribute label on MPLS is divided into two types; those are Label Distribution Protocol (LDP) and Traffic Engineering (TE). LDP is a basic routing protocol used in MPLS network, using label switching. TE is a technique to manipulate network traffic to control the traffic load on the network. With the differences of MPLS mechanism using LDP and TE, indubitably the way of working and the performance of those routing protocol are also different. Graphical Network Simulator 3 (GNS 3) is employed to simulate MPLS using LDP and TE with Brawijaya University (UB) topology. Examination scenario are performed by sending package between 2 local networks outside the main network of UB's topology. The parameters are round trip delay to find out delivery speed and convergence time to know the speed of choosing the best route to reach destination when dead link occurs at delivery process. The purpose of this research is to compare the performance of MPLS using LDP and TE on the computer network routers. The results are, MPLS using TE has better performance because the delivery uses the explicit route on the tunnel. There's no need to search for designated router as used in MPLS LDP that makes the router looking for the best path when branching occurs. Using backup route also helps MPLS using TE to reduce convergence time when failure occurs at the delivery of the package.